Aos leitores: as estratégias de autorreferencialidade no editorial de Veja - Weschenfelder, Aline (Universidade do Vale do Rio dos Sinos, 2011)
The research seeks to study the self-referential strategies invested in the editorial of the magazine Veja that allow the creation of bonds of trust and credibility with your audience. Describes the profile of opinionated journalism from the recounting of stories of production processes with emphasis on its employees, as reporters andphotographers during their routine work. To classify the types of speeches declared by section examined, the texts are divided into categories. A detailed quantitative analysis performed on the issues of 2009, he was elected a "professional celebration" as a parameter for qualitative analysis. Compares the editorial "Letter from the Editor" and "Letter to the Reader" by presenting their characteristics, and talks are on their relationships with other sections of the magazine, as the images accompanying editorial looking to prove what is being said in their texts. Brands are identified in the self-referential of Veja discourses, characterized as enunciating subject who, through persuasion, and, implicitly encourages, the reader to surrender to its dictates.
Keywords: Autorreferencialidade; Editorial; Jornalismo opinativo; Revista Veja; Self-referential; Opinionated journalism; Magazine Veja; ACCNPQ::Ciências Sociais Aplicadas::Comunicação